Mitochondrial biogenesis during gametogenesis and embryonic development - Reynier, Pascal (Henry Stewart Talks, 2007)
Mitochondrial biogenesis and mass, Mitochondrial biogenesis in spermatogenesis, Mitochondrial biogenesis in oogenesis, The bottleneck theory, Maternal transmission of mitochondrial DNA, Influence of the mitochondrial DNA content on fertilization, Mitochondrial biogenesis in early embryonic development, Mitochondrial transfer in reproduction
Archived at 2018/09/26